Relational Quasicontractions and Related Fixed Point Theorems - Nidal H. E. Eljaneid; Faizan A. Khan; Hamid I. A. Mohammed; Aftab Alam (Journal of Mathematics)
In this article, some results on fixed points under quasicontractions in the framework of metric space endowed with binary relation are proved. Our newly proved results improve and extend several noted fixed point theorems of the existing literature besides their relation-theoretic analogues. We conclude this article by constructing an example to affirm the efficacy of our results.